Depression, anxiety, and stress in women following acute cardiac syndrome: implications for secondary prevention - DiGiacomo, Michelle; Davidson, Patricia; Vanderpluym, A.; Snell, R.; Worrall-Carter, L. (Elsevier Inc, 2007)
Objective: To document incidence of depression, anxiety, and stress in women more than six months following an acute coronary syndrome. Design: Participants were identified from a coronary care unit database. The Depression Anxiety Stress Scales 21 (DASS 21) was sent to potential participants via postal survey. Setting: A metropolitan teaching hospital in Melbourne, Australia Participants: The cohort of women was aged between 55 and 70 years. They had been admitted to hospital with a diagnosis of acute coronary syndrome (ACS) between 6 - 14 months prior to participating in this study. Main Outcome Measures: Scores on Depression, Anxiety, and Stress Scale (DASS 21) Results: Of the 117 posted questionnaires, thirty-nine women with a mean age of 63 (SD 4.97) responded to the survey, representing a response rate of 33.3%. Most participants scored within normal levels of depression (66.7%), anxiety (60.5%), and stress (70.3%), however, mild to extremely severe levels of each construct (33.4%, 39.6%, and 29.7%, respectively) were found. Conclusions: The reporting of elevated levels of depression, anxiety and stress in a subset of women more than six months following an ACS event underscores the importance of ongoing screening for risk factors impacting on psychological well-being and the inclusion of this information in education and counseling strategies in both the inpatient and outpatient settings. Based on these pilot data, consideration of a screening system in the immediate post discharge period for women at risk and an education or support service are recommended.